ROS produced in mitochondria entrapped by self-assembly peptide fibers for target therapy of glioma - Suling Zhang; Fanchen Yu; Yang Yang; Yi Jia; Yongqiang Xu; Jin Zhou; Zeng-Ying Qiao; Jin Lu; Chunmei Li; Hao Wang; Junbai Li (Proceedings of the National Academy of Sciences, 2026)
Brain glioma is a highly energy-dependent malignant tumor. Sonodynamic therapy (SDT) provides a noninvasive and effective approach for brain glioma therapy. Reactive oxygen species (ROS) from sonosensitizers in the treatment of SDT play a key role. Inspired by spider webs, a self-assembling “spider peptide” (P1) bearing porphyrin moieties was constructed to generate ROS under ultrasound. In glioma cells, P1 forms web-like nanofibers that weave around mitochondria and enables ROS to release in situ. This efficiently disrupts the energy metabolism of mitochondria leading to the inhibition of glioma cells growth. Glioma-derived exosomes loaded with peptide P1 (Evs@P1) exhibit enhanced blood–brain barrier permeability and homotypic targeting to glioma cells. After endocytic uptake, Evs@P1 complexes undergo hydrolysis in the acidic lysosomal environment exposing the mitochondrial-targeting peptide. Ultrasound enhances the rate of peptide self-assembly into nanofibers, which are extruded from the exosomes and weave around the mitochondrial surface. Such an assembly of P1 nanofibers accelerates the ROS generation, which is 3.7 times higher than that in the monomeric state. It indicates an effective method to prevent glioma growth in mice brains in vivo.